2011
DOI: 10.1016/j.neurobiolaging.2009.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C is released in association with exosomes: A new tool of neuronal communication which is unbalanced in Alzheimer's disease

Abstract: It has recently become clear that proteins associated with neurodegenerative disorders can be selectively incorporated into intraluminal vesicles of multivesicular bodies and subsequently released within exosomes. Multiple lines of research support a neuroprotective role for cystatin C in Alzheimer's disease (AD). Herein we demonstrate that cystatin C, a protein targeted to the classical secretory pathway by its signal peptide sequence, is also secreted by mouse primary neurons in association with exosomes. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 33 publications
3
76
0
Order By: Relevance
“…It has been previously shown that a fraction of intracellular Ab can be released through exosomes by neurons and oligodendrocytes. 32,[45][46][47] In addition, phagocytosed Ab has been found to be re-secreted from microglia, although through an undefined mechanism. 48 We now show that microglia release neurotoxic Ab 1-42 and Ab 1-40 species in association with MVs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that a fraction of intracellular Ab can be released through exosomes by neurons and oligodendrocytes. 32,[45][46][47] In addition, phagocytosed Ab has been found to be re-secreted from microglia, although through an undefined mechanism. 48 We now show that microglia release neurotoxic Ab 1-42 and Ab 1-40 species in association with MVs.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles can be formed by budding from plasma membrane, or originated from multivesicular endosomes or multivesicular bodies (MVBs) (Tkach and Thery 2016). Neurons can release exosomes that contain functionally active proteins and miRNAs, which can exert a neuroprotective or neurotoxic role (Ghidoni et al 2011; Janas et al 2016; Lachenal et al 2011; Morel et al 2013). Recent several reviews offer the roles of exosomes and microvesicles in normal function, the development of regeneration of CNS as well as in the onset and progression of of some neurodegenerative and neuroinflammatory diseases (Janas et al 2016; Porro et al 2015).…”
Section: Endogenous Protective Mechanisms and Secreted Help-me Sigmentioning
confidence: 99%
“…Importantly, uptake of CysC occurs in cells other than the cell producing the protein (Ekstrom et al, 2008; Kolodziejczyk et al, 2010; Merz et al, 1997), suggesting that in vivo CysC can mediate important roles between cells through its uptake in target cell populations. CysC is also secreted in association with exosomes (Ghidoni et al, 2011), small lipid-membrane delineated extracellular vesicles (EVs) generated within late endosomes/multivesicular bodies (Lakkaraju and Rodriguez-Boulan, 2008; Simpson et al, 2008). Exosomes are stable vesicles, protecting their content from degradation, have the potential of transporting their content long distances within the extracellular space, and can be internalized by cells other than the cell responsible for their generation [reviewed in (Lakkaraju and Rodriguez-Boulan, 2008; Simpson et al, 2008)].…”
Section: Introductionmentioning
confidence: 99%